Prospective multicenter clinical trial to evaluate the safety and effectiveness of a new glistening-free one-piece acrylic toric intraocular lens - Packer M (Dove Medical Press, 2018)
Mark Packer,1 Jon I Williams,2 Gregg Feinerman,3 Richard S Hope2 On behalf of the enVista Toric Clinical Study Group 1Mark Packer MD Consulting, Inc., Boulder, CO, USA; 2Surgical Clinical and Medical Affairs, Bausch & Lomb Inc., Irvine, CA, USA; 3Feinerman Vision Center, Newport Beach, CA, USA Purpose: Glistening formation in the intraocular lens (IOL) optic has the potential to impact quality of vision. The enVista One-Piece Hydrophobic Acrylic Spherical IOL Model MX60 (MX60 IOL) is currently the only US Food and Drug Administration-approved IOL with a label of “no glistenings”. The purpose of this prospective, multicenter, partially randomized, partially controlled, double-masked, pivotal study was to evaluate the safety and effectiveness of the enVista One-Piece Hydrophobic Acrylic MX60T Toric IOL (enVista MX60T Toric IOL). Patients and methods: Subjects (n=191) were implanted with the enVista MX60T Toric IOL (cylinder powers 1.25, 2.00, or 2.75 D) or the parent MX60 IOL (control). Eyes within the lowest range of corneal astigmatism were randomized to receive either Toric 1.25 D IOL or control IOL in a 1:1 ratio. All subjects with corneal astigmatism requiring 2.00 or 2.75 D cylinder IOLs received toric IOLs. Rotational stability, cylinder reduction, and best-corrected distance visual acuity were primary effectiveness endpoints measured at Visit 4 (120–180 days postoperatively). Results: Visit 4 mean absolute axis misalignment in the All Toric group was 4.68°±7.33°, and all subjects had ≤5° absolute rotation from Visit 3 to Visit 4. The 1.25 D group had significantly greater improvement in dioptric cylinder reduction (P<0.001), percent cylinder reduction (P<0.001), and mean uncorrected distance visual acuity (P<0.001), compared to control at Visit 4. Most adverse events (AEs) were mild, with no serious AEs in the study eyes. The rates of cumulative AEs through Visit 4 were below International Organization for Standardization (ISO) standard 11979-7 AE rates. Conclusion: enVista MX60T Toric IOL is safe and effective for patients with preoperative corneal astigmatism undergoing IOL implantation. Keywords: human, IOL, astigmatism, cataract, enVista, clinical